Strategic environmental assessment for priority basins of the colombian andes: dilemmas, challenges and necessities (2014)
ABSTRACT In Colombia many rivers and other inland aquatic systems, especially into the Andean Region (the most populated of the country), suffer several anthropogenic impacts related to land use and land cover compromising their water quality and quantity, and the provision of other goods and ecosystem services for the future. It is imperative that the Colombian government may initiate new and updated policies, plans, programs in constant consultation and cooperation with other institutions, civilian and environmental authorities, and researchers from the country (or elsewhere), to obtain amply responsibility on the sustainable river management, especially in this region. Thus, a more integrative watershed river assessment and related riverine issues are necessaries for the current freshwater use and management, and before that new development projects going to start. Decision